Amplification of UV radiation and gain mechanisms in ZnO films with loose-packed structure - L.A. Zadorozhnaya; A.P. Tarasov; A.S. Lavrikov; V.M. Kanevsky (Компьютерная оптика)
The modern demands for miniaturization of optoelectronic devices, in particular, for the UV range, are inextricably linked with the improvement of fabrication technologies for the corresponding photonic nano/micro objects and the study of their radiative properties. In this work, the method of pyrolytic carbothermal synthesis, which is a modification of the thermal evaporation method, was used to fabricate microcrystalline ZnO films with laser properties. The influence of the size and packing type of ZnO microcrystallites in the films on their emissive properties were revealed. The films with relatively large microcrystallites (10–15 µm in size on average) were found to exhibit UV amplified spontaneous emission at room temperature. The possibility of additional enhancement of this emission and its two-threshold behavior in loose-packed regions of such films were found for the first time. It was shown that the observed phenomenon is due to the competition between two gain mechanisms, which are assumed to arise predominantly in different regions of microcrystallites as a result of exciton-phonon and exciton-electron interaction processes. As the temperature decreases, the dominant gain mechanism gradually changes to exciton-exciton scattering, regardless of the type of film structure. The results obtained open up the possibilities of the thermal evaporation synthesis to a wider extent and can be useful in interpreting the optical gain mechanisms in ZnO micro- and nanostructures.